Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Prove the Identity: sin^3 A + cos^3 A / sin A + cos A = 1 - sin A cos A?
1 Answer
- germanoLv 74 years ago
Hello,
(sin³A + cos³A) /(sinA + cosA) = 1 - sinA cosA
let's factor the numerator at the left side as a sum of cubes:
[(sinA + cosA)(sin²A - sinA cosA + cos²A)] /(sinA + cosA) = 1 - sinA cosA
let's simplify:
sin²A - sinA cosA + cos²A = 1 - sinA cosA
finally let's apply the fundamental identity sin²A + cos²A = 1:
(sin²A + cos²A) - sinA cosA = 1 - sinA cosA
1 - sinA cosA = 1 - sinA cosA (Q.E.D.)
I hope it helps